Model Misinterpretation within Biology: Phenotypes, Statistics, Networks, and Inference - Kliebenstein, Daniel J. (Frontiers in Plant Science, 2012)
Models of myriad forms are rapidly becoming central to biology. This ranges from statistical models that are fundamental to the interpretation of experimental results to ODE models that attempt to describe the results in a mechanistic format. Models will be more and more essential to biologists but this growing importance requires all model users to become more sophisticated about what is in a model and how that limits the usability of the model. This review attempts to relay the potential pitfalls that can lay within a model